Identification of Phytochemicals, Antioxidant Activity Using DPPH Method (1.1=Diphenyl-2-Picrylhydrazyl), Toxicity Using Brine Shrimp Lethality Test of Diplazium esculentum Tea - Habibi Habibi; Armyn Nurdin; Agussalim Bukhari; Suryani As’ad (AIBPM Publisher, 2022)
Vegetable fern/pakis/paku (Diplazium esculentum) contains active compounds such as total phenols, steroids, triterpenoids, flavone amino acids, and flavonoids, which are rich sources of medically necessary phytochemicals. This study aimed to determine the potential antioxidant content of pakis (Diplazium esculentum) tea. The research methods used included the antioxidant test procedure (IC50), DPPH method, phytochemical procedure, and BSLT procedure. The results of the phytochemical test showed a positive (+) value on the alkaloid, flavonoid, saponin, and phenolic test. The DPPH test showed 130.38468, 131.1340, 131.5681 ppm with an average value of 131.0289 ppm; meanwhile, moderate antioxidant activity and BSLT testing showed LC50 of 9817.479 ppm, where the tea was found not toxic since the LC50 value <1000 ppm. Based on the findings, the brewed vegetable fern/pakis (Diplazium esculentum) contains alkaloids, flavonoids, saponins, and phenolics based on phytochemical testing, potential as a non-toxic antioxidant source according to DPPH and BSLT tests. Diplazium esculentum is a vegetable that contains antioxidants and is safe for consumption.Keywords: Antioxidant activity, BSLTDiplazium esculentum, DPPH, Phytochemicals